Associations between home learning environment and mental health for young children living in China. Issue 3 (4th May 2018) - Lee, Kyunghee; Xie, Xiaoqing
ABSTRACT: This study examines the impact of home learning environments on Chinese children's mental health. The Home Observation for the Measurement of Environments was used to measure the degree to which children's home learning environments are cognitively stimulating and emotionally nurturing . The Devereux Early Childhood Assessment (DECA) was used to assess children's mental health as indicated by protective factors and behavioral concerns. A convenience sampling method was used to collect data from 137 Chinese mothers living in China who had children ages 3–5. The questions addressed in this paper are as follows: 1) Does the parental provision of home learning environments differ depending on baseline characteristics? 2) Does the parental provision of home learning environments affect children's mental health (protective/resilience factors and behavioral concerns)? Baseline characteristics such as child's gender, maternal age and marital status were associated with parental provision of home learning environments. Children of mothers who provided a cognitively stimulating learning environment were more likely to have higher protective/resilience factors and fewer behavioral concern factors.